Modern Pedagogical Approaches and Pedagogical Opportunities for Determining Their Impact on Educational Effectiveness - Muradova, Z. K.; Khaydarova, O. K.; Temirova, G. Z. (Jurnal Teknologi Pendidikan, 2025)
This study examines the role of modern pedagogical approaches in the educational process and evaluates their effectiveness in developing learners’ knowledge, skills, and competencies. It analyzes the pedagogical potential of applying concepts such as interactive methods, the constructivist approach, the competency-based approach, as well as differentiated and individualized instruction. The study substantiates the role of these approaches in enhancing learning activity, increasing student motivation, and fostering independent thinking. The research focuses on the methodological foundations of contemporary pedagogy, innovative educational technologies, and practical implementation mechanisms, identifying internal and external factors that influence educational quality. As a result, the pedagogical opportunities manifested in the impact of modern approaches on educational effectiveness are scientifically generalized.